2013
DOI: 10.1039/c3cc46545d
|View full text |Cite
|
Sign up to set email alerts
|

In situ atomic imaging of coalescence of Au nanoparticles on graphene: rotation and grain boundary migration

Abstract: Using in situ transmission electron microscopy, we demonstrated that gold nanoparticles are unified via "oriented attachment" assisted either by nanoparticle rotation or grain boundary migration at the attachment interface. We also observed that the combined nanoparticle changes shape with stable facet planes via surface diffusion, along with recrystallization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 22 publications
6
85
2
Order By: Relevance
“…Interestingly, the two Au clusters are merged directly at the atomic scale, which can be attributed to the epitaxy between the clusters and YSZ. Such behavior is in striking contrast to the unification of Au nanocrystals, which is assisted by crystal rotation or grain boundary migration2324. Moreover, the whole coalescence process is completed rapidly in 210 s (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Interestingly, the two Au clusters are merged directly at the atomic scale, which can be attributed to the epitaxy between the clusters and YSZ. Such behavior is in striking contrast to the unification of Au nanocrystals, which is assisted by crystal rotation or grain boundary migration2324. Moreover, the whole coalescence process is completed rapidly in 210 s (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The characteristic sintering time by surface diffusion is τnormals=knormalBTrp,04CDγa4 where k B is the Boltzmann constant, T (K) is the temperature, r p,0 (m) is the particle radius, C is a constant ( C = 25), D (m 2 /s) is the diffusion coefficient, γ (N/m 2 ) is the surface tension and α (m) is the atomic size. Yuk et al observed by in situ transmission electron microscope (TEM) images of electron beam irradiated Au nanoparticles (3–7 nm) that they sinter by oriented attachment which occurs either by three‐dimensional particle orientation or by grain boundary migration, depending on particles’ contact orientation.…”
Section: Theorymentioning
confidence: 99%
“…Sintering results in multiple grains (polycrystalline particles) that are wiped out and transform into a single crystal at sufficiently long times. The results are compared with electron beam irradiation experiments of coalescing Au nanoparticles . Besides free‐standing Au nanoparticle coalescence, these simulations are quite relevant also to sintering of Au on ceramic oxide supports that do not exhibit strong affinity or metal support interactions, such as Ag on TiO 2 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the coalescence of reduced Sn NPs happens to a limited extent, which is consistent with the unchanged morphologies before and after carbonization (Figure S2) . Besides, the partial grain boundaries of the Sn cores resulting from particle adhesion can be clearly observed, and they are marked by yellow dashed lines in Figure d …”
Section: Resultsmentioning
confidence: 91%